High levels of serum superoxide dismutase as a biomarker of intrahepatic cholestasis of pregnancy in patients with viral hepatitis B - Fei Wang; Yajuan He; Naijuan Yao; Litao Ruan; Zhen Tian (BMC, 2022)
Abstract Background Intrahepatic cholestasis of pregnancy (ICP) is characterized by skin pruritus and impaired liver function. Hepatitis B virus (HBV) infection increases the risk of developing ICP. HBV infection is associated with oxidative stress, which has been proven to participate in the development of ICP. The goal of this study was to explore the relationship among HBV, oxidative stress, and ICP, and investigate whether a biomarker of oxidative stress may predict the diagnosis and severity of ICP. Methods We induced a retrospective cohort of 70 ICP patients from January 2019 to December 2020, and compared their data with those from healthy pregnant women (n = 70). Serum levels of an oxidative stress marker superoxide dismutase (SOD) were examined using an enzyme-linked immunosorbent assay (ELISA). Diagnostic and prognostic values of serum SOD were analyzed by receiver operating characteristic (ROC) curve. Results Pregnant women in the ICP group had significantly higher level of serum SOD (243.24 ± 12.57 U/L vs 98.70 ± 2.95 U/L, p < 0.01) and a higher rate of HBV infection (51.53% vs 25.71%, p < 0.05) compared with the control group. HBsAg-positive ICP patients had a higher levels of serum SOD (287.24 ± 19.21 U/L vs 196.65 ± 11.75 U/L, p < 0.01) compared with HBsAg-negative ICP patients. A serum SOD level > 121.4 U/mL might be used to predict ICP, while a serum SOD level > 274.6 U/mL might predict ICP severity. Conclusion HBV infection promotes oxidative stress during the pathogenesis of ICP. Serum levels of SOD could be used to predict ICP diagnosis and severity. Modification of oxidative stress might be a treatment target for ICP.